COST-EFFECTIVE CLOUD SOLUTIONS: OPTIMIZING RESOURCE UTILIZATION AND EXPENDITURE - Ashok Mohan Chowdhary Jonnalagadda, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This thorough article looks at methods for obtaining affordable cloud solutions while maximizing resource use and upholding performance requirements. It examines several important techniques, such as serverless architectures, reserved instance management, auto-scaling implementations, resource right-sizing, and multi-cloud tactics. The article shows how companies can use systematic optimization techniques to increase operational efficiency while cutting waste by analyzing real-world implementations and industry studies. It also discusses typical cloud cost management issues, such as performance balancing, complexity management, and cultural resistance, offering workable answers and industry best practices for each. The article assesses key performance indicators and important success metrics that businesses can use to gauge and enhance their cloud cost optimization initiatives. Organizations can achieve substantial cost savings while preserving or enhancing their operational skills and service quality by fully executing these techniques.